Effect of Fear of Falling on Mobility Measured During Lab and Daily Activity Assessments in Parkinson’s Disease - Atrsaei, Arash; Hansen, Clint; Elshehabi, Morad; Solbrig, Susanne; Berg, Daniela; Liepelt-Scarfone, Inga; Maetzler, Walter; Aminian, Kamiar (Frontiers in Aging Neuroscience, 2021)
In chronic disorders such as Parkinson’s disease (PD), fear of falling (FOF) is associated with falls and reduced quality of life. With inertial measurement units (IMUs) and dedicated algorithms, different aspects of mobility can be obtained during supervised tests in the lab and also during daily activities. To our best knowledge, the effect of FOF on mobility has not been investigated in both of these settings simultaneously. Our goal was to evaluate the effect of FOF on the mobility of 26 patients with PD during clinical assessments and 14 days of daily activity monitoring. Parameters related to gait, sit-to-stand transitions, and turns were extracted from IMU signals on the lower back. FOF was assessed using the Falls Efficacy Scale-International (FES-I) and patients were grouped as with (PD-FOF+) and without FOF (PD-FOF-). Mobility parameters between groups were compared using logistic regression as well as the effect size values obtained by the Wilcoxon rank sum test. The peak angular velocity of the turn-to-sit transition of the timed-up-and-go test had the highest discriminative power between PD-FOF+ and PD-FOF- (r-value of effect size = 0.61). Moreover, PD-FOF+ had a tendency towards lower gait speed at home and a lower amount of walking bouts, especially for shorter walking bouts. The combination of lab and daily activity parameters reached a higher discriminative power (AUC = 0.75) than each setting alone (AUC = 0.68 in the lab, AUC = 0.54 at home). Comparing the gait speed between the two assessments, the PD-FOF+ showed higher gait speeds in the capacity area compared to their TUG test in the lab. Mobility parameters extracted from both, lab and home-based assessments, contribute to the detection of FOF in PD. This study adds further evidence to the usefulness of mobility assessments that include different environments and assessment strategies. Although this study was limited in the sample size, it still provides a helpful method to consider the daily activity measurement of the PD patients into clinical evaluation. The obtained results can help the clinicians for a more accurate prevention and treatment strategy.